BRIDGING THE GAP BETWEEN MENTAL AND PHYSICAL HEALTH THE EFFICACY OF INTEGRATED PSYCHOSOCIAL INTERVENTIONS IN FAMILY MEDICINE (Journal of Medical & Health Sciences Review, 2025)
Background: While there is increasing understanding about the reciprocal relationship between mental and physical health, family medicine continues to have a significant unmet need for the integration of psychosocial treatments. Many patients with chronic medical conditions have comorbid psychological problems that are either undetected or untreated and contribute to overall health status and health service use.Objective: The intention of this study was to assess the effectiveness of integrated psychosocial interventions on mental health outcomes, physical symptom management, and patient satisfaction in the context of family medicine.Method: A quasi-experimental pre-test-younger siblings test design was used that included 180 adult patients diagnosed with chronic conditions (e.g., diabetes, hypertension) and comorbid mild-to-moderate anxiety or depression. Participants were randomly allocated to standard care vs standard care and 8-week psychosocial intervention (intervention group: CBT-based sessions, stress management and motivational interviewing). Outcome measurements were assessed using the Hospital Anxiety and Depression Scale (HADS), the Patient Health Questionnaire-ED (PHQ-ED), the PHQ-9, and physical health indicators.Results: The intervention group achieved a substantial increase in psychological well-being (mean HADS decrease 6.3, p < 0.01), reduction in PHQ-9 scores (mean decrease 5.1, p < 0.01), and gained better control of physical symptoms (e.g., systolic BP and HbA1c decrease). Similarly, patient satisfaction with care was significantly greater in the intervention group (p < 0.05).Conclusions: Adding psychosocial interventions to FH care brings about considerably better mental and physical health results, highlighting the importance of comprehensive patient treatment in primary care.